2014
DOI: 10.1093/annonc/mdu116
|View full text |Cite
|
Sign up to set email alerts
|

Optimal treatment of early-stage ovarian cancer

Abstract: There is evidence of a long-term benefit of adjuvant post operative chemotherapy for early-stage ovarian cancer. The magnitude of benefit is greatest in patients at a higher risk of recurrence defined as stage 1B/1C grade 2/3, any stage 1 grade 3 or clear cell histology. The use of single agent carboplatin is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 24 publications
2
57
0
5
Order By: Relevance
“…Recurrent disease was detected in 19% of the patients, which is consistent with the recurrence rates reported in other studies (10-30%) [6,7,13,25,26,27]. In the present study, adjuvant chemotherapy was not significantly associated with RFS and OS regardless of the staging procedure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recurrent disease was detected in 19% of the patients, which is consistent with the recurrence rates reported in other studies (10-30%) [6,7,13,25,26,27]. In the present study, adjuvant chemotherapy was not significantly associated with RFS and OS regardless of the staging procedure.…”
Section: Discussionsupporting
confidence: 92%
“…The 10-year results of the ICON1 study, which were published recently, showed an advantageous long-term effect of adjuvant chemotherapy in high-risk tumors [27]. …”
Section: Discussionmentioning
confidence: 99%
“…In accordance with available data, 5,6 Danish guidelines suggest adjuvant chemotherapy to stage IA and IB serous carcinoma, grade 2/3 and all clear cell and all (1988) stage IC. 7 In the presented material, however, we did not have individual data on chemotherapy, but we assume that most IC1 patients received chemotherapy as recommended.…”
Section: Stage Imentioning
confidence: 71%
“…A switch of chemotherapy regimens from carboplatin-paclitaxel to pegylated liposomal doxorubicincarboplatin might reduce the toxicity 21 . Additionally, a reduction in the number of adjuvant chemotherapy cycles from 6 to 3 in patients with high-risk epithelial ovarian cancer did not result in a higher recurrence rate and was associated with reduced toxicity 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Proper staging of presumed early-stage ovarian cancer is important starting point, because adjuvant chemotherapy could be withheld in many patients with early-stage disease 21,23 . Hence, adequate staging, specifically of patients with figo ia and ib disease, could avoid longterm side effects when chemotherapy is withheld in those patients.…”
Section: Discussionmentioning
confidence: 99%